De quelques pratiques universitaires de littéracie. Discours croisés d’étudiants et d’enseignants sur l’écriture en sciences de l’éducation - Isabelle Delcambre et Yves Reuter (Éducation et Socialisation)
This study is part of a research which aims first to a better understanding of the writing academic practices of students and teachers secondly to describe their links. The writings are considered as disciplinary genres. So we may take into account the effects upon these writing practices, these helps to writing, these assessments...of being set into a particular disciplinary. In this paper, we focus upon the elements whose specificity to the writings produced inside the « sciences de l’éducation » appears through comparisons with some others academic disciplines, such as « Psychologie » or « Histoire. » These results are based on analysis of discourses of students and teachers, collected by the way of questionnaires and focus groups.